2017
DOI: 10.1002/aoc.3901
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous silica SBA‐15 functionalized with acidic deep eutectic solvent: A highly active heterogeneous N‐formylation catalyst under solvent‐free conditions

Abstract: Mesoporous silica SBA-15 functionalized with N-methylpyrrolidonium-zinc chloride based deep eutectic solvent (DES) is found to be a more efficient and reusable catalyst for a convenient N-formylation of a variety of amines at room temperature.N-Formylation of primary, secondary as well as heterocyclic amines have been carried out in good to excellent yields by treatment with formic acid in low loading of DES/SBA-15 an environmentally benign catalyst for the first time. The DES/SBA-15 catalyst, which possesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 49 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…In their other study, Azizi et al [53] prepared the same catalyst and utilized for the N-formylation of a variety of amines that are valuable intermediates ( Figure 7). They reported that the catalyst was efficient for both primary, secondary and heterocyclic amines and could be recycled for many times without a significant loss of activity.…”
Section: Reactions Catalysed By Lewis Acid Type Dessmentioning
confidence: 99%
See 1 more Smart Citation
“…In their other study, Azizi et al [53] prepared the same catalyst and utilized for the N-formylation of a variety of amines that are valuable intermediates ( Figure 7). They reported that the catalyst was efficient for both primary, secondary and heterocyclic amines and could be recycled for many times without a significant loss of activity.…”
Section: Reactions Catalysed By Lewis Acid Type Dessmentioning
confidence: 99%
“…N-formylation of variety of amines. e e See Azizi et al[53] for detailed reaction components and conditions.…”
mentioning
confidence: 99%
“…Presumably, the mechanism of the reaction proceeds through activation of carbonyl group of formic acid in situ by the action of SO 3 H group of nanocatalyst. 47,48 In the rst step, the SO 3 H proton of the nanocatalyst interacts with the oxygen atom of the carbonyl group of the formic acid, thereby increasing the electrophilic character of the carbonyl carbon probably through hydrogen bond formation. Then, the lone pair of electron on the nitrogen atom of aniline attack the cationic carbon of formic acid.…”
Section: Proposed Reaction Mechanismmentioning
confidence: 99%
“…Recently, they have drawn the attention of the academic community because they can be employed as highly‐efficient organic synthesis media 7–9 . Despite the numerous superiorities of these catalysts, their widespread industrial application has been restricted by several limitations, including the need for relatively large amounts of LADESs, homogeneity, lack of reusability, and high‐cost processes 10–13 . On the other hand, heterogeneous DES catalysts can offer several advantages for organic reactions, including ease of separation, efficient recovery reusability and simple implementation 14–16 …”
Section: Introductionmentioning
confidence: 99%